2015
DOI: 10.1101/gad.267609.115
|View full text |Cite
|
Sign up to set email alerts
|

LEDGF/p75 interacts with mRNA splicing factors and targets HIV-1 integration to highly spliced genes

Abstract: The host chromatin-binding factor LEDGF/p75 interacts with HIV-1 integrase and directs integration to active transcription units. To understand how LEDGF/p75 recognizes transcription units, we sequenced 1 million HIV-1 integration sites isolated from cultured HEK293T cells. Analysis of integration sites showed that cancer genes were preferentially targeted, raising concerns about using lentivirus vectors for gene therapy. Additional analysis led to the discovery that introns and alternative splicing contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
144
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(157 citation statements)
references
References 57 publications
11
144
1
1
Order By: Relevance
“…3F). Consistent with a recent report (42), LKO changed the shape of the entire curve, with integration now highly favored within the initial 30% and disfavored to below the MRC for latter halves of genes (Fig. 3F).…”
Section: −26supporting
confidence: 91%
See 3 more Smart Citations
“…3F). Consistent with a recent report (42), LKO changed the shape of the entire curve, with integration now highly favored within the initial 30% and disfavored to below the MRC for latter halves of genes (Fig. 3F).…”
Section: −26supporting
confidence: 91%
“…6, WT cell). LKO was reported recently to decrease integration into genes enriched for intron content to near random (42). Interestingly, we found that CPSF6 more prominently affected integration into intron-dense genes than did LEDGF/ p75 (Fig.…”
Section: Cpsf6 Directs Hiv-1 Integration To Active Genes and Ledgf/p75supporting
confidence: 49%
See 2 more Smart Citations
“…It is not surprising, therefore, that retroviruses evolved genus-specific and contrasting traits with respect to the types of chromosomal loci they preferentially target. HIV-1, a highly pathogenic lentivirus, channels integration toward genedense chromosomal domains, integrating predominantly within active transcription units (4,5). Recent studies uncovered a hierarchical mechanism that depends on HIV-1 capsid, the major viral structural protein (a product of the viral gag gene), and integrase, which interact with cellular proteins CPSF6 and LEDGF/p75, respectively (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%